1990
DOI: 10.1002/ana.410270211
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow during focal seizures of temporal and frontocentral onset

Abstract: Ictal single photon emission computed tomography recordings were performed in 9 patients in the course of 11 seizures. Injections of radionuclide were made an average of 72 seconds after the onset of the seizure as indicated by electroencephalography. All patients also underwent interictal recordings. In 6 patients, the localization of the electroencephalographic focus and the morphological lesions corresponded with the ictal hyperperfusion. This could be seen in single photon emission computed tomography. Sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
3

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 9 publications
4
46
0
3
Order By: Relevance
“…Sensitivity ranged from 88.9% (ExT group) to 92.9% (TLE group) for ictal studies and from 76.7% (TLE group) to 78.3% (ExT group) for interictal studies, which is comparable to reported results for HMPAO 10,13,[26][27][28][29][30]. Also, specificity values of "mTc-ECD SPECT, ranging from 52.2% (ExT group, interictal studies) to 92.9% (TLE group, ictal studies), are similar to those found by Spencer (3) in a comprehensive meta-analysis of brain SPECT in epilepsy.…”
Section: Discussionsupporting
confidence: 85%
“…Sensitivity ranged from 88.9% (ExT group) to 92.9% (TLE group) for ictal studies and from 76.7% (TLE group) to 78.3% (ExT group) for interictal studies, which is comparable to reported results for HMPAO 10,13,[26][27][28][29][30]. Also, specificity values of "mTc-ECD SPECT, ranging from 52.2% (ExT group, interictal studies) to 92.9% (TLE group, ictal studies), are similar to those found by Spencer (3) in a comprehensive meta-analysis of brain SPECT in epilepsy.…”
Section: Discussionsupporting
confidence: 85%
“…Single photon emission computed tomography (SPECT) (or PET) shows reduction in cerebral blood flow interictally but is less sensitive to medial temporal lobe epilepsy than PET measurement of metabolism, in the vicinity of S70% (61)(62)(63). SPECT measurement of ictal blood flow increases, however, is very sensitive, and is apt to be more circumscribed than interictal hypoperfusion or hypometabolism if the injection of radioligand is made early in the seizure (63)(64)(65)(66). It is of interest that these functional imaging studies usually have not demonstrated bilateral abnormalities in MTLE, despite MRI findings of bilateral hippocampal atrophy in -10-15% of patients, and bilateral pathologic and EEG findings in up to 80% of patients.…”
Section: Developmental Acquired Medial Temporal Lobe Epilepsy Localmentioning
confidence: 99%
“…Interictal, ictal, and postictal patterns of regional cerebral blood flow (rCBF) are well described (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Patterns of rCBF in extratemporal seizures characterized in recent publications (15)(16)(17)(18)(19)(20)(21) suggest that regional cerebral perfusion (rCP) patterns in extratemporal seizures differ from those that occur during mesial temporal lobe seizures.…”
mentioning
confidence: 99%